Analysis of Ethyl p-Methoxycinnamate from Kaempferia galanga L. Extract by High Performance Liquid Chromatography - Wiwin Winingsih; Sri Gustini Husein; Rozalia Putri Neno Ramdhani (Journal of Tropical Pharmacy and Chemistry, 2021)
Ethyl para-methoxycinamate (EPMS) is a major compound of Kaempferia galanga L that has anti-inflammatory effect. The purpose of this study was to determine of EPMS in Kaempferiae galanga L rhizome extract by High Performance Liquid Chromatography (HPLC) and evaluated the performance of the analysis. This study included determination of system suitability, accuracy, precision, linearity and range, limit of detection (LOD) and Limit of quantitation (LOQ) and selectivity. The results of system suitability test HPLC System for EPMS analysis were as follows isocratic elution system of a mobile phase mixture of methanol: water (70:30) containing 0.1% TFA, uv detector at a wavelength of 308 nm using column C18 (150 × 4, 6mm, 5?m) flow rate 1 ml / min. From the analysis, it was found that the average EPMS content was 78.74%. Then method had linear concentration range from 5-360 ppm, with R ² = 0.9999. The LOD and LOQ were 7.0722 ppm and 21.4311 ppm respectively. The accuracy of this method that represented by % recovery was 98.02% - 101.26%. The precision of this method that expressed by Relative Standard Deviation (RSD) was 1.57%. The selectivity of this method that showed by resolution value was 2.6. Based on the results of the system suitability test and analysis performance evaluation,all parameters met the requirements.